Ininterrotti transiti : Arte di fine secolo. - Vergine, Lea (Milano : Rizzoli International Publications New York, 2001)
Abramovic, Marina ; Alÿs, Francis ; Arroyo, Eduardo ; Barney, Matthew ; Beecroft, Vanessa ; Beuys, Joseph ; Blank, Irma ; Bravi, Giannetto ; Bugli, Enrico ; Burri, Alberto ; Calle, Sophie ; Castellani, Enrico ; Cattelan, Maurizio ; Cavaliere, Alik ; Costa, Claudio ; Cragg, Tony (Anthony) ; Duchamp, Marcel ; Fabre, Jan ; Fabro, Luciano ; Ferrer, Esther ; Fiore, Gerardo Di ; Gabellone, Giuseppe ; Garzoni, Giovanna ; Gilbert & George ; Habicher, Edouard ; Hatoum, Mona ; Hill, Gary ; Holzer, Jenny ; Horn, Rebecca ; Kahlo, Frida ; Kapoor, Anish ; Kiefer, Anselm ; Kosuth, Joseph ; Kounellis, Jannis ; Kruger, Barbara ; Leatherdale, Marcus ; LeWitt, Sol ; Long, Richard ; Luca ; Mainolfi, Luigi ; Malevich, Kasimir ; Manzoni, Piero ; Maraniello, Giuseppe ; Marclay, Christian ; de Maria, Walter ; Mauri, Fabio ; Merz, Mario ; Moorman, Charlotte ; Morimura, Yasumasa ; Nagasawa, Hidetoshi ; Neshat, Shirin ; Nunzio ; Opie, Catherine ; Oppenheim, Meret ; Paladino, Mimmo ; Pane, Gina ; Parmiggiani, Claudio ; Pascali, Pino ; Penone, Giuseppe ; Perino & Vele ; Persico, Mario ; Picasso, Pablo ; Pierre et Gilles ; Pisani, Gianni ; Pistoletto, Michelangelo ; Poirier, Anne & Patrick ; Ponte, Amalia Del ; Popova, Liubov ; Psihoyos, Louie ; Rama, Carol ; Rennie, Charles ; Serrano, Andres ; Sherman, Cindy ; Staccioli, Mauro ; Stepanova, Varvara ; Tatafiore, Ernesto ; Taylor-Wood, Sam ; Toyen ; Trotta, Antonio ; Warhol, Andy ; Werefkin, Marianne von ; Whiteread, Rachel ; Witkin, Joel-Peter
Italiaans
boek